Exercise Training Activates AMPK to Improve Metabolic-Associated Fatty Liver Disease: Research Progress - Bu Qiao; Jie Liu (Ilmu Inovasi Nusantara, 2026)
Metabolic-associated fatty liver disease (MAFLD) is a metabolic disorder characterized by excessive hepatic lipid accumulation and is closely associated with insulin resistance, chronic low-grade inflammation, and mitochondrial dysfunction. Exercise training is a key non-pharmacological strategy that improves the hepatic metabolic milieu and may slow disease progression, yet the underlying molecular mechanisms remain incompletely clarified. This review aims to synthesize, from the perspective of energy metabolism regulation, the potential mechanisms by which exercise ameliorates MAFLD through activation of AMP-activated protein kinase (AMPK), thereby providing a theoretical basis for optimizing exercise-based interventions. A literature review approach was adopted. Systematic searches were conducted in major English-language academic databases, including Web of Science and PubMed, using keywords related to exercise training, MAFLD, and AMPK. Representative recent basic and clinical studies were screened and integrated to summarize relevant signaling pathways and physiological outcomes. The evidence indicates that exercise-induced AMPK activation suppresses de novo lipogenesis while promoting fatty acid oxidation, thereby reducing intrahepatic lipid deposition. Exercise may also improve mitochondrial function and enhance mitophagy, lowering oxidative stress and modulating inflammation-related signaling to attenuate chronic hepatic inflammation. Collectively, AMPK serves as a central regulatory node linking exercise stimuli to coordinated restoration of metabolic and inflammatory homeostasis in MAFLD. Future well-designed human studies and multidimensional evidence are warranted to clarify the pathway-specific effects of different exercise prescription components on AMPK signaling networks